2004
DOI: 10.1002/jnr.20315
|View full text |Cite
|
Sign up to set email alerts
|

(−)‐Epigallocatechin gallate inhibits lipopolysaccharide‐induced microglial activation and protects against inflammation‐mediated dopaminergic neuronal injury

Abstract: Microglial activation is believed to play a pivotal role in the selective neuronal injury associated with several neurodegenerative disorders, including Parkinson's disease (PD) and Alzheimer's disease. We provide evidence that (-)-epigallocatechin gallate (EGCG), a major monomer of green tea polyphenols, potently inhibits lipopolysaccharide (LPS)-activated microglial secretion of nitric oxide (NO) and tumor necrosis factor-alpha (TNF-alpha) through the down-regulation of inducible NO synthase and TNF-alpha ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
105
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 192 publications
(111 citation statements)
references
References 45 publications
5
105
0
Order By: Relevance
“…Flavonoid-rich blueberry extracts have been observed to inhibit NO, IL-1b and TNF-a production in activated microglia cells [53,54], whilst the flavonol quercetin [17], the flavones wogonin and bacalein [55], the flavanols catechin and epigallocatechin gallate (EGCG) [62], and the isoflavone genistein [125] have all been shown to attenuate microglia and/or astrocyte mediated neuroinflammation via mechanisms that include inhibition of: (1) iNOS and cyclooxygenase (COX-2) expression, (2) NO production, (3) cytokine release, and (4) NADPH oxidase activation and subsequent reactive oxygen species generation, in astrocytes and microglia. Flavonoids may exert these effects via direct modulation of protein and lipid kinase signalling pathways [98,105,130], for example via the inhibition of MAPK signalling cascades, such as p38 or ERK1/2 which regulate both iNOS and TNF-a expression in activated glial cells [9].…”
Section: Inhibition Of Neuroinflammationmentioning
confidence: 99%
“…Flavonoid-rich blueberry extracts have been observed to inhibit NO, IL-1b and TNF-a production in activated microglia cells [53,54], whilst the flavonol quercetin [17], the flavones wogonin and bacalein [55], the flavanols catechin and epigallocatechin gallate (EGCG) [62], and the isoflavone genistein [125] have all been shown to attenuate microglia and/or astrocyte mediated neuroinflammation via mechanisms that include inhibition of: (1) iNOS and cyclooxygenase (COX-2) expression, (2) NO production, (3) cytokine release, and (4) NADPH oxidase activation and subsequent reactive oxygen species generation, in astrocytes and microglia. Flavonoids may exert these effects via direct modulation of protein and lipid kinase signalling pathways [98,105,130], for example via the inhibition of MAPK signalling cascades, such as p38 or ERK1/2 which regulate both iNOS and TNF-a expression in activated glial cells [9].…”
Section: Inhibition Of Neuroinflammationmentioning
confidence: 99%
“…The structurallyrelated flavanone hesperetin and other flavonoids appear to be incapable of inhibiting pathways leading to NO production, although they have been found to partially alleviate neuroinflammation through the inhibition of TNFa production (103) . Flavonoids present in blueberry have also been shown to inhibit NO, IL-1b and TNFa production in activated microglia cells (104) , whilst the flavonol quercetin (105) , the flavones wogonin and bacalein (106) , the flavanols catechin and epigallocatechin gallate (107) and the isoflavone genistein (108) have all been shown to attenuate microglia-and/or astrocyte-mediated neuroinflammation via mechanisms that include inhibition of, in astrocytes and microglia: (1) iNOS and cyclooxygenase 2 expression; (2) NO production; (3) cytokine release; (4) NADPH oxidase activation and subsequent reactive oxygen species generation. All these effects appear to depend on an ability to directly modulate protein kinase and lipid kinase signalling pathways (45,46) .…”
Section: Inhibition Of Neuroinflammationmentioning
confidence: 99%
“…Thus far, studies have indicated that flavanols [72,105], flavones [34,87,99,151,186], and flavonols [35] are all capable of inhibiting the release of NO…”
Section: Extracellular Signal-regulated Protein Kinase Pathwaymentioning
confidence: 99%